The Poems of Catullus an annotated translation - Catullus, Gaius Valerius ca. v84-v55; Uzzi, Jeannine Diddle 1971-; Thomson, Jeffrey (Cambridge Univ. Press, 2015)
"The Roman poet Catullus is one of the most popular and frequently studied ancient authors. His poems were written just over two thousand years ago during the chaotic but culturally vibrant final decades of the Republic and deal with themes of passion and grief, friendship and enmity, politics, literature and myth. This new translation, the product of a collaborative effort between a classicist and a poet, allows modern readers to experience his poems rather as his ancient Roman audience did. The poems are presented as contemporary and concise with a new energy and pace that both enhance Catullus' appeal for non-specialists and challenge specialists to consider his work from a fresh perspective. Extensive notes are provided, as well as an introduction which takes account of modern poetics and popular culture. The translation will appeal not only to classicists but also to lovers of literature in general and poetry in particular. "This approach to translation may have been good for students of Latin, but it has prevented Catullus from gaining the widespread appeal of poets like Homer, Sappho, and Vergil. Catullus' style is uncannily modern, his concerns timeless; in fact, as Martin himself notes, Catullus is probably the only classical poet to have had significant influence on modern English poetry (xxii). In recent history, however, Catullus been approached as a poet tied tightly to his historical context, ancient Rome of the late Republic, and useful primarily to students of Latin and classics"..